2009
DOI: 10.4049/jimmunol.0803256
|View full text |Cite
|
Sign up to set email alerts
|

Impaired CD4 and CD8 Effector Function and Decreased Memory T Cell Populations in ICOS-Deficient Patients

Abstract: Interaction of ICOS with its ligand is essential for germinal center formation, T cell immune responses, and development of autoimmune diseases. Human ICOS deficiency has been identified worldwide in nine patients with identical ICOS mutations. In vitro studies of the patients to date have shown only mild T cell defect. In this study, we report an in-depth analysis of T cell function in two siblings with novel ICOS deficiency. The brother displayed mild skin infections and impaired Ig class switching, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 71 publications
(102 reference statements)
6
96
0
2
Order By: Relevance
“…These results also correlate with clinical observations in ICOS-deficient patients, whose CD4 + T cells exhibit normal IL-2 production but reduced secretion of the cytokines IL-4, IFN-γ, IL-10, and IL-17 upon in vitro stimulation, as well as a decreased percentage of CD4 + central and effector memory T cells (32). Interestingly, the percentage of ICOS hi CD4…”
Section: Discussionsupporting
confidence: 76%
“…These results also correlate with clinical observations in ICOS-deficient patients, whose CD4 + T cells exhibit normal IL-2 production but reduced secretion of the cytokines IL-4, IFN-γ, IL-10, and IL-17 upon in vitro stimulation, as well as a decreased percentage of CD4 + central and effector memory T cells (32). Interestingly, the percentage of ICOS hi CD4…”
Section: Discussionsupporting
confidence: 76%
“…ICOS deficiency in humans precipitates either immunodeficiency or autoimmunity, indicating its importance in immunoregulation (37). Through adoptive transfer studies, we confirmed that ICOS-expressing CD4 + cells from the cervical LNs of Protollin-treated mice were capable of inhibiting the development of allergic airway disease, indicating that the TLR4-dependent induction of ICOS via the nasal mucosa can inhibit lower airway allergic disease.…”
Section: Icossupporting
confidence: 52%
“…Thus, we hypothesized that nasal application of Protollin would inhibit experimental asthma by promoting Th1 or Treg responses. ICOS is expressed by all of the aforementioned T cell subsets and is important in the differentiation (35), effector (36,37), proliferative (38), migratory (39) and memory (40) functions of T cells. A number of recent reports have shown that ICOS expression on Tregs enhances the function, proliferation and survival of these cells and has critical immunoregulatory implications (41).…”
mentioning
confidence: 99%
“…This role of ICOS in TA-Treg biology is supported by the fact that (i) ICOS þ Treg have a stronger suppressive function in melanoma (46) and murine models (27,28), and (ii) ICOS deletion in human (22) and mice (23) correlates to a decreased Treg proportion.…”
Section: Discussionmentioning
confidence: 74%
“…Identified in 1999 (18), ICOS, a T cell costimulatory molecule of the CTLA4/PD1/CD28 family, plays a nonoverlapping function with CD28 (19) on CD4 þ T cells. In particular, ICOS is critical in the regulation of humoral response (20) through its role on T follicular helper cell activation as illustrated in ICOS KO mice (21) and deficient patients (22). ICOS expression has also been linked with Treg maintenance in mice (23) and mucosal tolerance (24).…”
Section: Introductionmentioning
confidence: 99%